Implementasi Etnopedagogi dalam Pendidikan Berbasis Kearifan Lokal di Ubud - Ni Putu Yuniarika Parwati; I Wayan Suastra; Ida Bagus Putu Aryana (Program Studi Pendidikan Ekonomi Universitas PGRI Mahadewa Indonesia, 2025)
The application of ethnopedagogy in Ubud can help integrate Balinese cultural values ​​into the education system, so that students not only gain academic knowledge, but also a deep understanding of the values ​​and traditions that shape their identity. Considering that Indonesia is a pluralistic country with various ethnic groups and ethnicities, which of course have different cultures, ethnopedagogical-oriented learning is very important to implement. This research uses a qualitative approach with a case study design. The results of this research are that ethnopedagogy as an educational approach based on local wisdom has a strategic role in preserving culture amidst the challenges of globalization. By integrating local values, traditions and wisdom into learning, this approach not only increases academic understanding but also strengthens students' cultural identity. In Ubud, the application of ethnopedagogy based on the Tri Hita Karana philosophy and local artistic and cultural heritage has proven effective in instilling the values ​​of mutual cooperation, solidarity and social responsibility. The implementation of ethnopedagogy faces significant challenges, such as foreign cultural influences, cultural commercialization, lack of formal documentation, and limited integration into formal curricula. To overcome these obstacles, close collaboration is needed between educational institutions, government and local communities. Support through policies, cultural documentation, and curriculum adjustments are important steps to ensure that cultural values ​​can continue to be passed on.